1996
DOI: 10.1021/ic960465j
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Chalcogen−Nitrogen Interactions:  Molecular and Electronic Structures of Geometrical Isomers of the Diazenes RSNC(R‘)NNC(R‘)NSR

Abstract: The sulfur-containing diazenes ArSNC(Ar‘)NNC(Ar‘)NSAr (1d, Ar = Ar‘ = 4-CH3C6H4; 3b, Ar = Ph, Ar‘ = 2-BrC6H4; 3c, Ar = Ph, Ar‘ = 2-CF3C6H4) are obtained by the reaction of Ar‘CN2(SiMe3)3 with 3 molar equivs of ArSCl in CH2Cl2. X-ray structural determinations have shown that 1d exists as a Z,E,Z isomer with a weak intramolecular S···N interaction [2.607(10) Å], whereas 3b adopts an E,E,E configuration. Crystals of 1d are monoclinic, space group P21/n, with a = 6.140(2) Å, b = 10.492(6) Å, c = 20.728(9) Å, β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…Indeed, theoretical studies on a series of chalcogen containing diazenes undoubtedly demonstrated the important role of the p type orbital interactions in the stabilization of intramolecular EÁ Á ÁN contacts. 26 It is thus clear that in the case of our TTF-SMe-OX the stabilization of This demonstrates once again that the 3c-4e model accurately describes also the NÁ Á ÁS nonbonded interaction in our case.…”
Section: Theoretical Study On Neutral Ttf-oxsupporting
confidence: 60%
See 1 more Smart Citation
“…Indeed, theoretical studies on a series of chalcogen containing diazenes undoubtedly demonstrated the important role of the p type orbital interactions in the stabilization of intramolecular EÁ Á ÁN contacts. 26 It is thus clear that in the case of our TTF-SMe-OX the stabilization of This demonstrates once again that the 3c-4e model accurately describes also the NÁ Á ÁS nonbonded interaction in our case.…”
Section: Theoretical Study On Neutral Ttf-oxsupporting
confidence: 60%
“…Indeed, theoretical studies on a series of chalcogen containing diazenes undoubtedly demonstrated the important role of the p type orbital interactions in the stabilization of intramolecular EÁÁÁN contacts. 26 It is thus clear that in the case of our TTF-SMe-OX the stabilization of 20 ; r B = electron density at the BCP (au); r 2 r B = Laplacian at the BCP (au). planar structures, be they s-cis or s-trans, is largely favored also by p interactions such as p(S)-p(CQC) and p(CQC)-p(CQN).…”
Section: Theoretical Study On Neutral Ttf-oxmentioning
confidence: 90%
“…Divalent chalcogen atoms frequently engage in SBIs with other atoms that contain lone pairs of electrons [10,11], these interactions are the result of a combination of electrostatic, covalent, and dispersion contributions that overcome the strong Pauli repulsion between lone pairs [12][13][14]. A thorough computational (DFT) study of the association of 1,2,5-chalcogenadiazoles showed that the covalent interactions represent the largest contribution to the stabilization of the (E-N) 2 supramolecular synthon.…”
Section: The Nature Of the E-n Sbimentioning
confidence: 99%
“…1). The fundamentals of this model derived from empirical observation have been validated by modern quantum mechanical methods [15,16] but a complete bonding description does require the inclusion of all orbital, electrostatic and dispersion contributions [6]. While mixing of occupied and unoccupied orbitals corresponds to the donor-acceptor character of the interaction and confers directionality to the SBI, an unavoidable destabilizing contribution (the Pauli repulsion) results from the mixing of all-occupied orbitals.…”
Section: Introductionmentioning
confidence: 99%